2019
DOI: 10.1002/jac5.1178
|View full text |Cite
|
Sign up to set email alerts
|

2019 Update to the American College of Clinical Pharmacy Pharmacotherapy Didactic Curriculum Toolkit

Abstract: Introduction The American College of Clinical Pharmacy (ACCP) Pharmacotherapy Didactic Curriculum Toolkit was created by the 2008 ACCP Educational Affairs Committee to provide guidance to schools and colleges of pharmacy for didactic pharmacotherapy curricular development. The toolkit was revised and updated by the 2016 ACCP Educational Affairs Committee. Objectives In accordance with the ACCP Board of Regents decision to update the toolkit every 3 years, the 2019 ACCP Publications Committee was charged with u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(68 citation statements)
references
References 17 publications
(22 reference statements)
0
61
0
Order By: Relevance
“…Respondents were asked if their school’s non-experiential curriculum prepared them to deprescribe in clinical practice; this was more likely to be endorsed by students that received deprescribing curriculum exposure. The low percentage of students that reported deprescribing as part of their pharmacy school curriculum and the high percentage of content being delivered in lectures highlights the opportunity for growth and expansion of deprescribing education in required pharmacy school curricula [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Respondents were asked if their school’s non-experiential curriculum prepared them to deprescribe in clinical practice; this was more likely to be endorsed by students that received deprescribing curriculum exposure. The low percentage of students that reported deprescribing as part of their pharmacy school curriculum and the high percentage of content being delivered in lectures highlights the opportunity for growth and expansion of deprescribing education in required pharmacy school curricula [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent survey of American schools and colleges of pharmacy found that respondent schools spent a median of six contact hours teaching geriatric pharmacotherapy [ 21 ]. As a concept, deprescribing first appeared in the American College of Clinical Pharmacy (ACCP) Pharmacotherapy Didactic Toolkit in the recently published 2019 update as a Tier 1 topic (highest priority) [ 22 , 23 ]. Recently, clinical practice guidelines have developed processes to address the deprescribing of specific agents or classes of agents, however, there is no present guidance applying these guidelines to PharmD programs [ 17 , 24 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…13 The American College of Clinical Pharmacy (ACCP) has a pharmacotherapy didactic curriculum toolkit that provides guidance on the ID topics that need to be covered during pharmacy training. 20 Also, the World Health Organization has a published curricula guide for health care education and training on antimicrobial resistance, including pharmacy education. 21 A review conducted by Chahine and colleagues introduced a model to engage pharmacy students in AMS where authors proposed timing and means of introduction of AMS concepts for pharmacy students, residents and fellows.…”
Section: A J P Ementioning
confidence: 99%
“…Elective research opportunities can drastically impact a student's interests and career trajectories. Currently, there are recommendations available for pharmacy curriculum therapeutics courses within the “2019 Update to the American College of Clinical Pharmacy Pharmacotherapy Didactic Curriculum Toolkit”; however, there is no guidance for other areas of study (ie, clinical research) 20,21 . As a result, significant heterogeneity exists across colleges of pharmacy regarding integration of clinical research into the curriculum 22‐24 .…”
Section: Elective Research Opportunities For the Pharmacy Studentmentioning
confidence: 99%